Sloterdijk; neuroglobalización, stressors and psycho-immunological practices - Vásquez Rocca, Adolfo (Nómadas. Critical Journal of Social and Juridical Science, 2013)
We explore the comprehensive program to experiment with one's body, a method that finds its basis in the idea of romantic medicine where, according to Sloterdijk, the dose effects in the healthy and the sick were reflected in a mirror. This is where an ambitious originates semiotics of pharmacological medication, not only endomorfinismo of speculation, but quimioéticos endocrine mechanisms. In the human sphere there are no less than three immune systems, which work overlaid with a strong cooperative assembly and functional complementarity. On the biological substrate, largely automated and independent of consciousness, have been developed in man, in the course of their mental and sociocultural, two supplementary charge of a proactive development of potential damages: first, a system of socio-immune practices, especially legal or solidarity, but also the military, with which men develop, in "society", their confrontations with foreign aggressors and distant neighbors and offenders or harmful, on the other hand , a system of symbolic practices or psycho-immunological, with whose help men succeed, since time immemorial, coping fairly well their vulnerability to the destination, including mortality, based on imaginary antelaciones and use of a series mental arms.
Keywords: immunology; communications; anthropotechnics; biopolitics; neuroglobalización